AUTHENTICATION OF PLANTS USED IN TRADITIONAL CHINESE MEDICINE– CHALLENGES AND OPPORTUNITIES - Simmonds, M. S. J.; Leon, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Plants have played an important role in traditional Chinese medicine (TCM). This talk will provide an overview of how Kew has gone about developing a collection of species of TCM plants that can be used as standards to check the identity and quality of plants entering the trade in Britain. The collection contains samples for DNA based bar -coding, chemical fingerprinting and anatomical analysis as well as traditional taxonomic specimens. The talk will cover the challenges posed by changes in the sale of over-the-counter herbal medicines in Europe and the need for similar collections to cover the wide scope of traditional medicines being traded in Europe.